2022
DOI: 10.1021/acsnano.2c01872
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Nanoplastics Toxicity to Zebrafish: Dysregulation of the Brain–Intestine–Microbiota Axis

Abstract: In animal species, the brain–gut axis is a complex bidirectional network between the gastrointestinal (GI) tract and the central nervous system (CNS) consisting of numerous microbial, immune, neuronal, and hormonal pathways that profoundly impact organism development and health. Although nanoplastics (NPs) have been shown to cause intestinal and neural toxicity in fish, the role of the neurotransmitter and intestinal microbiota interactions in the underlying mechanism of toxicity, particularly at environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 80 publications
3
35
0
Order By: Relevance
“…In this study, life-cycle exposure of parental zebrafish to environmentally realistic concentrations of differently charged PS altered spontaneous movements at 24 hpf and heart rate at 48 hpf for offspring. These results are consistent with previous results reported for zebrafish exposed for 30 days to PS–NPs, which resulted in adverse effects on the development of offspring through dysregulation of the brain-intestine-microbiota axis . These results demonstrate transgenerational effects of exposure to differently charged PS that result in adverse effects on reproduction through epigenetics, which could affect the development of the F1 generation due to lower concentrations of VTG and alterations of expressions of genes through methylation of DNA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, life-cycle exposure of parental zebrafish to environmentally realistic concentrations of differently charged PS altered spontaneous movements at 24 hpf and heart rate at 48 hpf for offspring. These results are consistent with previous results reported for zebrafish exposed for 30 days to PS–NPs, which resulted in adverse effects on the development of offspring through dysregulation of the brain-intestine-microbiota axis . These results demonstrate transgenerational effects of exposure to differently charged PS that result in adverse effects on reproduction through epigenetics, which could affect the development of the F1 generation due to lower concentrations of VTG and alterations of expressions of genes through methylation of DNA.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous results reported for zebrafish exposed for 30 days to PS−NPs, which resulted in adverse effects on the development of offspring through dysregulation of the brain-intestine-microbiota axis. 31 These results demonstrate transgenerational effects of exposure to differently charged PS that result in adverse effects on reproduction through epigenetics, which could affect the development of the F1 generation due to lower concentrations of VTG and alterations of expressions of genes through methylation of DNA. The reproductive endocrine system is complex and can be affected and modulated by interacting factors.…”
Section: ■ Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Interestingly, several recent studies focused on the potential effects induced by NPLs in the intestinal microbiome of freshwater secondary consumers. It has been found that both MPs and NPLs may cause dysbiosis in the zebrafish gut at very low concentrations (1 µg/L), but NPLs can also increase the presence of pathogenic genera, such as Aeromonas [131] . It has also been found that PS-NPLs at concentrations ≤ 0.1 mg/L affected the brain-intestine-microbiota axis of zebrafish, causing reduced growth, inflammatory responses, and altered intestinal permeability, even inducing transgenerational effects such as NPL accumulation in the gastrointestinal tract of the offspring [132] .…”
Section: Toxicity Towards Freshwater Secondary Consumersmentioning
confidence: 99%